Comparison between Electroplating and Electroless on Plastic Surface - J.M. Slaiman, Qassim; A. Slman, Khlas (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
We report a method of converting non-conductive plastic surfaces into conductive by plating either copper electroless or copper electroplating -carbon black containing bending Agent onto Perspex plastics . Various approaches have been studied in order to comparing properties of the plated copper for two methods such as scanning electron microscopy (SEM),thickness, roughness, porosity, tensile Strength and elongation. The results show that the surface of electroplating was uniform, compact, and continuous and it had an obvious metallic sheen, while the surface of plated copper for electroless for it had many pores. Also observed that the coating was composed of small cells. These cells have been deposited together closely. Thick copper layer was deposited a(38μm ) electroplating while (5μm) for electroless plating tensile strength and elongation of copper electroplating became greater compared with copper electroless, whereas the roughness and Porosity became smaller.The electroplating copper deposition process developed in this study may open up a new route of plating on plastics (POP) for printed circuit boards, electromagnetic interference shielding, and many other applications.